Thermodynamic study of the effect of partial thermal reduction of dysprosium oxide on solar-to-fuel energy conversion efficiency - Rahul R. Bhosale (6467102) (2020)
A thermodynamic equilibrium and efficiency analysis of the dysprosium oxide-based solar thermochemical H2O splitting (Dy-WS) cycle is conducted. The objective of this study is to understand the effect of partial thermal reduction (TR) of Dy2O3 on the solar-to-fuel energy conversion efficiency (ηsolar to fuel Dy WS) of the Dy-WS cycle. The equilibrium analysis indicate a rise in the percentage TR of Dy2O3 (%TR-Dy) from 0.3% up to 100% when the TR temperature (TH) is increased from 2000 K to 2530 K. The upsurge in the TH yielded a considerable surge in the Qsolar reactor Dy WS and Qsolar heater Dy WS. Overall results of this study showed that theηsolar to fuel Dy WS is amplified from 0.6% to 6.5% in three zones (slow zone, medium-fast zone, and fast zone) as the TH is amplified from 2000 K up to 2280 K. A further rise in the TH from 2280 K up to 2530 K resulted in a drop in theηsolar to fuel Dy WS from 6.5% to 3.5%. By employing the heat recuperation, theηsolar to fuel HR Dy WS is improved further up to 11.4% (at TH = 2280 K). Other Information Published in: Fuel License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.fuel.2020.118249